Complete mitochondrial genome sequence of a xerophilic fungus, Aspergillus pseudoglaucus. Issue 2 (3rd July 2019) - Park, Jongsun; Kwon, Woochan; Huang, Xiaoxiao; Mageswari, Anbazhagan; Heo, In-Beom; Han, Kap-Hoon; Hong, Seung-Beom
Abstract: Aspergillus pseudoglaucus is a xerophilic filamentous fungus which can produce various secondary metabolites. Here, we reported the complete mitochondrial genome sequence of A. pseudoglaucus isolated from Meju, a soybean brick in Korea. Its mitochondrial genome was successfully assembled from raw reads sequenced using MiSeq by Velvet and SOAPGapCloser. Total length of the mitochondrial genome is 53, 882 bp, which is third longest among known Aspergillus mitochondrial genomes and encoded 58 genes (30 protein-coding genes including hypothetical ORFs, two rRNAs, and 26 tRNAs). Nucleotide sequence of coding regions takes over 66.6% and overall GC content is 27.8%. Phylogenetic trees present that A. pseudoglaucus is located outside of section Nidulantes . Additional researches will be required for clarifying phylogenetic position of section Aspergillus .